Modernism keywords - Cuddy-Keane, Melba; Hammond, Adam; Peat, Alexandra (Keywords in literature and culture (KILC), 2014)
Modernism: Keywords presents a series of short entries explaining the diverse and often contradictory meanings of words used with frequency and urgency in "written modernism"--Provided by publisher.